2021
DOI: 10.1002/acr2.11346
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Ultrasound for Giant Cell Arteritis: Establishing a Protocol Using Vascular Sonographers in a Fast‐Track Clinic in the United States

Abstract: Objective. We developed a fast-track clinic (FTC) to expedite the evaluation of patients suspected of having giant cell arteritis (GCA) using vascular ultrasound. Though FTCs have demonstrated efficacy in Europe, no protocolized clinic in the United States has been developed. This study introduces a new FTC model unique to the United States, using vascular sonographers, and describes the protocols used to develop reliable findings. We evaluate clinical outcomes using vascular ultrasound and temporal artery bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A recent study of 430 patients with suspected GCA found moderate agreement between sonographers (intra‐class correlation coefficient 0.61, 95% confidence interval [CI] 0.48‐0.75), similar to pathologists reporting temporal artery biopsies (0.62, 95% CI 0.49‐0.76) 10 . Fast‐track ultrasound clinics for GCA assessment in Europe, and more recently in northern America, have demonstrated promising results 11,12 …”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…A recent study of 430 patients with suspected GCA found moderate agreement between sonographers (intra‐class correlation coefficient 0.61, 95% confidence interval [CI] 0.48‐0.75), similar to pathologists reporting temporal artery biopsies (0.62, 95% CI 0.49‐0.76) 10 . Fast‐track ultrasound clinics for GCA assessment in Europe, and more recently in northern America, have demonstrated promising results 11,12 …”
Section: Introductionmentioning
confidence: 82%
“… 10 Fast‐track ultrasound clinics for GCA assessment in Europe, and more recently in northern America, have demonstrated promising results. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, high resolution ultrasound of the temporal arteries (tempUS), a diagnostic modality facilitating fast track approaches in order to avoid ocular ischaemic complications before treatment onset, is nowadays recommended as first line diagnostic imaging at least in European countries (7,8). In the USA, temporal artery biopsy is still considered as first line diagnostic approach, but currently efforts are undertaken on establishing sonographic imaging in the diagnostic workup of GCA (6,9). Colour duplex sonography of the axillary arteries (axUS) has been shown to detect involvement of the extracranial arteries in a considerable number of patients (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…This cutoff has been used in other studies, including by our group. 6 In 2011, Ghinoi et al 7 defined subclavian vasculitis as hypoechoic circumferential wall thickening ≥1.3 mm, although they noted that concerning findings <1.5 mm were rare. Recently, Ješe et al 8 determined that wall thickening ≥1.0 mm was highly sensitive and specific in their single-center prospective cohort in Slovenia, although notably the sensitivity of ultrasound in this study was very different from other ultrasound in GCA studies such as the TABUL study (98.4% vs. 54%, respectively).…”
mentioning
confidence: 99%